2005
DOI: 10.1111/j.1460-9568.2005.03944.x
|View full text |Cite
|
Sign up to set email alerts
|

Different responsiveness of striatonigral and striatopallidal neurons to L‐DOPA after a subchronic intermittent L‐DOPA treatment

Abstract: Early gene induction by L-DOPA in the striatum of dopamine denervated rats represents a useful way to study long-term modifications produced by this drug. The effects of acute and subchronic L-DOPA administration on zif-268 mRNA expression were compared in 6-hydroxydopamine-lesioned rats. Rats received a subchronic intermittent L-DOPA (6 mg/kg) treatment, which produces behavioural sensitization, a correlate of dyskinetic movements. Three days after interruption of subchronic treatment, zif-268 mRNA was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 66 publications
(76 reference statements)
4
42
0
Order By: Relevance
“…L-DOPA could stimulate D 1 receptors on striatonigral neurons (Gerfen et al, 1990), so to activate the "direct" pathway (Robertson and Robertson, 1989;Carta et al, 2005), or D 1 receptors on striatonigral nerve terminals (Starr, 1987;Aceves et al, 1991). The fact that TTX prevented the L-DOPA effect rules out this latter hypothesis, although it does not exclude an intranigral action of L-DOPA because this agent could stimulate GABAergic interneurons [dendritic location of D 1 receptors has been detected in the SNr (Huang et al, 1992)].…”
Section: Neurobiological Substrates Underlying J-113397/l-dopa Interamentioning
confidence: 89%
“…L-DOPA could stimulate D 1 receptors on striatonigral neurons (Gerfen et al, 1990), so to activate the "direct" pathway (Robertson and Robertson, 1989;Carta et al, 2005), or D 1 receptors on striatonigral nerve terminals (Starr, 1987;Aceves et al, 1991). The fact that TTX prevented the L-DOPA effect rules out this latter hypothesis, although it does not exclude an intranigral action of L-DOPA because this agent could stimulate GABAergic interneurons [dendritic location of D 1 receptors has been detected in the SNr (Huang et al, 1992)].…”
Section: Neurobiological Substrates Underlying J-113397/l-dopa Interamentioning
confidence: 89%
“…Altogether, these data suggest that dopamine D1/D5 receptors control GAD67 and GAD65 gene expression in striatonigral neurons via different signaling pathways. The expression of a number of transcription factors including ΔFosB or c-fos is upregulated in striatonigral neurons after systemic chronic l-DOPA or SKF-38393 administration to 6-OHDA-lesioned rats (Robertson et al, 1992;Doucet et al, 1996;Carta et al, 2005;Pavon et al, 2006;Valastro et al, 2007). Other recent studies have shown that the systemic administration of agonists of dopamine D1/D5 receptors is able to activate an extracellular-regulated kinase (ERK) pathway in striatonigral neurons in dopamine-depleted but not in intact unlesioned rats (Gerfen et al, 2002).…”
Section: Effects Of Dopamine D1/d5 Receptor Agonists On Striatonigralmentioning
confidence: 95%
“…Extensive studies in both rodent and nonhuman primate models, as well as studies in humans, suggest a role for the striatal opioid system in the development of LIDs (Morissette et al, 1997,Cenci et al, 1998,Duty et al, 1998,Henry et al, 1999,Johansson et al, 2001,Quik et al, 2002,Tel et al, 2002,Winkler et al, 2002,Henry et al, 2003,Carta et al, 2005,Aubert et al, 2006. Evidence for this possibility stems from results showing that enhanced PPE-B transcript levels correlate well with LIDs in experimental parkinsonian models and Parkinson's disease (Duty et al, 1998,Henry et al, 1999,Tel et al, 2002,Henry et al, 2003,Aubert et al, 2006.…”
Section: Discussionmentioning
confidence: 83%